2021
DOI: 10.3390/min11040422
|View full text |Cite
|
Sign up to set email alerts
|

Development of Mine Soils in a Chronosequence of Forestry-Reclaimed Sites in Eastern Kentucky

Abstract: Surface mining for coal has contributed to widespread deforestation and soil loss in coal mining regions around the world, and particularly in Appalachia, USA. Mined land reforestation is of interest in this and other regions where forests are the dominant pre-mining land use. This study evaluated mine soil development on surface-mined sites reforested according to the Forestry Reclamation Approach, representing a chronosequence of time ranging from 0 to 19 years after reclamation. Soils were sampled in depth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Soil fine (silt + clay) particle contents were increased over time since reclamation in an open‐pit coal mine dump in grassland area in this study, which had a positive effect on soil functions, especially moisture and nutrient retention (Sena et al, 2021). The increase of clay and silt in soil may be due to the increase of soil organic matter and soil nutrient status after reclamation in the open‐pit coal mine dumps of grassland area (Huang et al, 2016).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Soil fine (silt + clay) particle contents were increased over time since reclamation in an open‐pit coal mine dump in grassland area in this study, which had a positive effect on soil functions, especially moisture and nutrient retention (Sena et al, 2021). The increase of clay and silt in soil may be due to the increase of soil organic matter and soil nutrient status after reclamation in the open‐pit coal mine dumps of grassland area (Huang et al, 2016).…”
Section: Discussionmentioning
confidence: 62%
“…Soil TP, AP, AK and CEC had negative effects on soil bacterial community compositions while ACP, available nitrogen (AN), SOM, WAT, and sand content had positive effects on soil fungal community compositions. 4 | DISCUSSION 4.1 | Soil physic-chemical characteristics Soil fine (silt + clay) particle contents were increased over time since reclamation in an open-pit coal mine dump in grassland area in this study, which had a positive effect on soil functions, especially moisture and nutrient retention(Sena et al, 2021). The increase of clay and silt in soil may be due to the increase of soil organic matter and soil nutrient status after reclamation in the open-pit coal mine dumps of grassland area(Huang et al, 2016).…”
mentioning
confidence: 66%
“…For example, in this region, there are over 60 million ha of marginal lands, including an abundance of reclaimed mined land (Emery et al., 2017; Lemus & Lal, 2005), which offer unique challenges and opportunities for crop production and the accumulation of soil organic matter (SOM). Examples of the challenging soil characteristics of reclaimed mined lands related to both agronomic production and SOM stabilization include the presence of rock fragments (can be ∼50% of mineral soil), low clay content (<3%), compaction, relatively little topsoil and soil aggregation, low microbial activity, low pH, and the relatively low ability to store plant available water and essential nutrients (Haering et al., 2004; Johnson & Skousen, 1995; Sollins et al., 1996; Sena et al., 2021; Zipper et al., 2011). Despite these challenges, highly disturbed soils can sequester carbon (C) at higher rates compared to less disturbed soils due to lower initial organic C concentrations (Blanco‐Canqui, 2016; Lal, 2015; Paustien et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Data by WRI (2021) showed that Indonesia was the fourth-largest country to lose the tropical primary forest in 2021 with 202,905 ha. Deforestation and land-use conversion affect land quality, especially if the forest is converted into intensive agriculture and plantation areas (Li et al 2020;Naharuddin et al 2019;Sena et al 2021;Song 2017). Such conversion involves complex cultivation activities, including land clearing and preparation, intensive planting and maintenance, and harvesting which usually use heavy mechanical tools (Veldkamp et al 2020;Assefa et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Intensive agricultural practices have negative impacts on soil physical properties, such as the increase in soil bulk density and resistance to penetration, and decrease in soil aeration, aggregation stability and water infiltration, and therefore increase in the risk of soil erosion (Cherubin et al 2016b(Cherubin et al , 2017Hasannudin et al 2022). It takes a long time to improve soil quality following soil degradation due to intensive agriculture (Veldkamp et al 2020;Sena et al 2021). In this regard, agroforestry is an alternative land use option to recover soil conditions.…”
Section: Introductionmentioning
confidence: 99%